Design of single prism coded aperture snapshot spectral imager using ray tracing simulation - Ding, Mengjia; Yuen, Peter W. T.; Richardson, Mark A. (IEEE, 2019)
Novel imaging systems published in the literature mostly concern with the performance of the final stage of the designed system which normally accompanies with a brief description of the system configuration only. Other information, such as how the system was optimized and the methodology adopted for improving them to their final stage are heavily lacking in the open domain. This paper addresses this issue by providing a guide for the modeling of compressive imaging based on Single Disperser Coded Aperture Snapshot Spectral Imaging (SD-CASSI), with focuses on the optimization of the dispersion capability, the reduction of spatial and chromatic aberrations for enhancing the performance of the SD-CASSI. As an example the system is designed for a numerical aperture of 0.125, 0.3% distortion at central wavelength 587.56 nm, and 32 spectral bands with a spatial resolution of 13 μm. The system was simulated by ray tracing program TracePro.
Keywords: Apertures; Lenses; Imaging; Dispersion; Ray tracing; Image reconstruction; Wavelength measurement